P148 Once-daily tiotropium Respimat® add-on to at least ICS maintenance therapy reduces exacerbation risk in patients with uncontrolled symptomatic asthma. (12th November 2015) - Halpin, D; Bateman, ED; Paggiaro, P; Bleecker, ER; Engel, M; Moroni-Zentgraf, P; Schmidt, H; Kerstjens, HAM
Abstract : Background: A reduction in the risk of asthma exacerbation may provide improvements in clinical burden, patient experience and healthcare costs. In Phase III trials, once-daily tiotropium Respimat® add-on to at least ICS improved lung function in patients with symptomatic asthma. We investigated exacerbation risk in each trial. Methods: Five Phase III, double-blind, placebo-controlled, parallel-group trials in patients with symptomatic asthma. Patients received tiotropium Respimat® 5 µg or placebo Respimat® each as add-on to at least ICS maintenance therapy (Table 1 ). Pre-planned co-primary or secondary end points were time to first severe exacerbation and time to any asthma worsening. Results: Mean baseline% of predicted FEV1, ACQ-7 score and ICS dose (µg) were: 56.0 ± 13.1, 2.6 ± 0.7 and 1198 ± 539 in PrimoTinA-asthma® (two replicate trials); 75.1 ± 11.5, 2.2 ± 0.5 and 660 ± 213 in MezzoTinA-asthma® (two replicate trials); and 77.7 ± 11.9, 2.1 ± 0.4 and 381 ± 78 in GraziaTinA-asthma®. Tiotropium Respimat® 5 µg reduced risk of severe asthma exacerbation by at least 21% in all three severity cohorts (Table 1 ) and risk of asthma worsening versus placebo Respimat® in all trials, with a statistically significant reduction in PrimoTinA-asthma®. Conclusion: Once-daily tiotropium Respimat® 5 µg add-on to at least ICS maintenance therapy consistently reduced exacerbations across asthma severities and so may be a beneficial add-on option to reduce current and future exacerbation risk.